Identification of resonant vibrations of the miniature unmanned airplane with contact and non-contact measuring techniques. Issue 1 (January 2021) - Olejnik, Aleksander; Rogólski, Robert; Szczesniak, Michal
Abstract: The paper describes application of two different vibration measurement methods for identification of natural modes of the miniature UAV. The aim of this research was to determine resonant frequencies and modes of mini-airplane within specified range of frequency values. Special measuring equipment was used including both contact and non-contact techniques. The measuring systems on equipment of the Institute of Aviation Technology in the Faculty of Mechatronics, Armament and Aerospace of Military University of Technology (Warsaw, PL) were used to conduct measurements. In traditional GVT methods a large number of sensors can be attached to the aircraft. The weight of sensors and cables is negligible in relation to the mass of the large aircraft. But for small and lightweight unmanned aerial vehicles, this could bring a significant mass component in relation to the total mass of the tested object. In this paper the methodology of GVT was presented. Two different measuring methods were applied, i.e. the contact method and the non-contact method. Using the dedicated apparatus in relation to mini-airplane, properly prepared in terms of mass distribution, rudders deflection stiffness and proper support, some resonant characteristics can be determined. The contact measuring system consists of a multi-channel analyzer, piezoelectric accelerometers, electrodynamic exciters, amplifiers, impedance heads and a computer with the Test. Lab Software. As the non-contact method a laser scanning vibrometer was used. The principle of its operation is based on the separation of the emitted laser beam. The returning beam reflected from a vibrating object is captured by the camera and compared to the reference beam. Dedicated software analyses collected data and on the basis of it creates animations of structural vibrational shapes and spectral plots within investigated frequency range. Object used for research is the mini-UAV Rybitwa – composite mini-plane with a classic aerodynamic layout manufactured in IAT MUT. In the work both measurement methods and some sample results were presented. Results referenced to dynamic properties of the mini-UAV can be applied in the future to FE model tuning.